Application of a low-voltage direct-current electric field for lipid extraction from squid viscera. (20th December 2018) - Guo, Yanling; Huang, Wen-Can; Wu, Yufan; Qi, Xiangming; Mao, Xiangzhao
Abstract: Squid viscera are one of the predominant by-products of squid and its lipids and proteins are of high nutritional quality and economic value. The objective of this work was to evaluate an electrical treatment for efficient extraction of lipids from squid viscera. Electrical treatments were carried out with various electric field strengths (5 V/cm, 10 V/cm, and 15 V/cm) for different time durations. By using this electrical method, the lipid extraction efficiencies reached 71.2 ± 1.0%, 72.1 ± 1.2%, and 71.7 ± 1.5% at electric field strengths of 5 V/cm for 12 h, 10 V/cm for 2.5 h, and 15 V/cm for 50 min, respectively. The electrical method exhibited a powerful ability to disrupt the cell membrane, which was observed by scanning electron microscopy and confocal microscopy. In the meantime, crude proteins were also recovered from squid viscera. Altogether, this work clearly demonstrated that this electrical method is an efficient technique for lipid extraction from squid viscera. This study developed a new approach as an alternative to the traditional method to extract lipids from squid viscera. The application of a low-voltage direct-current electric field for lipid extraction from squid viscera is of great importance both from the view of environmental interests and economic interests, and provides new ideas for lipid extraction from other food wastes. Graphical abstract: Highlights: An electrical treatment was used for efficient extraction of lipids from squid viscera. The lipid extraction efficiency reached 71.7% in 50 min at 15 V/cm. Crude proteins were recovered from squid viscera. Amino acids obtained from squid viscera are complete and rich in content.